2013
DOI: 10.1155/2013/719407
|View full text |Cite
|
Sign up to set email alerts
|

The P66Shc/Mitochondrial Permeability Transition Pore Pathway Determines Neurodegeneration

Abstract: Mitochondrial-mediated oxidative stress and apoptosis play a crucial role in neurodegenerative disease and aging. Both mitochondrial permeability transition (PT) and swelling of mitochondria have been involved in neurodegeneration. Indeed, knockout mice for cyclophilin-D (Cyc-D), a key regulatory component of the PT pore (PTP) that triggers mitochondrial swelling, resulted to be protected in preclinical models of multiple sclerosis (MS), Parkinson's disease (PD), and amyotrophic lateral sclerosis (ALS). Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…In fact, several studies performed in p66Shc −/− cells show a decrease in intracellular ROS (Savino et al 2013;Trinei et al 2002), possibly explaining the observed protection against aging-associated diseases.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, several studies performed in p66Shc −/− cells show a decrease in intracellular ROS (Savino et al 2013;Trinei et al 2002), possibly explaining the observed protection against aging-associated diseases.…”
Section: Discussionmentioning
confidence: 93%
“…When CyPD-null mice are treated, they display a marked protection from axonal degeneration and a milder clinical picture despite a normal inflammatory response, thus providing strong evidence that PTP is involved in disease pathogenesis (193). A further indication of the central role played by the PTP in multiple sclerosis is provided by the observation that axonal damage of mice undergoing experimental autoimmune encephalomyelitis is reduced by genetic inactivation of p66Shc, which abrogates an important pathway of ROS-induced PTP opening (see above) (514).…”
Section: The Mitochondrial Permeability Transitionmentioning
confidence: 95%
“…In clinical trials, treatment with CsA at reperfusion reduced levels of the biomarkers troponin and mitochondrial creatine kinase (mtCK) and reduced total infarct size (Piot et al 2008). In many neurological disorders dysregulated Ca 2+ and ROS levels appear to have some component of injury mediated by increased mPTP opening, including excitotoxicity (Pivovarova and Andrews 2010), epilepsy (Jung et al 2012), Huntington’s disease (Quintanilla et al 2013), Alzheimer’s disease (Du et al 2011), Parkinson’s disease (Martin et al 2014b), Amyotrophic Lateral Sclerosis (Martin et al 2014a), and Multiple Sclerosis (Savino et al 2013). Conversely, it appears that susceptibility to mPTP opening is reduced in cancer, leading to cell resilience.…”
Section: Characteristics Of the Mptpmentioning
confidence: 99%